Eimeria hermani Farr, 1953 of the Canada goose, Branta canadensis : endogenous development, including intranuclear schizogony, in the domestic goose ( Anser anser domesticus ) - Skene, R. C.; Fernando, M. A. (Canadian Journal of Zoology, 1990)
All endogenous stages of Eimeria hermani were found throughout the small intestine of experimentally infected domestic goslings. At least two generations of schizogony were seen to occur prior to gamogony, and mature schizonts were seen from 36 to 84 h postinfection. Developing gamonts were seen between 96 and 120 h postinfection and oocysts were seen in histological sections by 132 h. All schizogonic stages occurred within the nuclei of epithelial cells whereas the sexual stages were found within the cytoplasm of epithelial cells. Infected nuclei appeared close to the brush border of epithelial cells, in contrast to the basal position occupied by uninfected nuclei. The schizonts and the resulting merozoites lay within a parasitophorous vacuole bounded by a vacuolar membrane. In infected nuclei a dissociation of the granular and fibrillar portions of the nucleolus was apparent and the heterochromatin was concentrated near the nuclear membrane. The ultrastructure of the merozoites is described and the intranuclear development of the asexual stages of E. hermani is discussed in relation to previously described intranuclear coccidian parasites.